Exploring the Impact of Entrepreneurial Orientation, Competitive Advantage, and Technological Factors on SMEs Digital Performance: A Comprehensive Analysis - Ridha Rizki Novanda; Hariz Eko Wibowo (Citakonsultindo, 2023)
SMEs have been lagging behind in the adoption of digital technologies, and the smaller the enterprise, the higher the risk of being left behind in the digital transition. Despite the potential benefits offered by emerging technologies, SMEs face challenges in fully embracing digital transformation. This study aims to analyze the influence of Entrepreneurial Orientation, Competitive Advantage, and Technological Factors on SMEs Digital Performance. The subjects of this study are SMEs business owners who have used digital marketing and have business licenses. 100 SMEs from all throughout Indonesia are the 100 samples. This study will use a convenience sample strategy by giving out questionnaires to SMEs actors in Indonesia. The Structural Equation Model (SEM) approach was used in this research. The technology element has a substantial impact on SMEs' digital performance, according to the results of hypothesis testing, with a P-Value of 0.005. Meanwhile, competition has no discernible impact on the digital performance of SMEs. How effectively digital-based SMEs market their products is influenced by a number of factors, including technology. Where perceived benefits, suitability, and cost indicate how digital marketing makes use of technology. Indonesian SMEs are very accustomed to using digital technology, especially social media, to advertise products that are available to a larger audience.